A curing additive, a low-impedance composite electrolyte containing the curing additive, and a safe semi-solid battery
By using the composite technology of polymer monomers I and II in the electrolyte, a cross-linked framework is constructed and specific groups are introduced, which solves the problem of high internal resistance of solid-state batteries and achieves a low-impedance and high-safe battery.
Patent Information
- Application Number
- CN202411519170.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing solid-state batteries have high internal resistance problems caused by polymer monomers, which limit their widespread promotion and use in practical applications.
By using the reciprocal combination of the curing additive polymer monomer I and polymer monomer II in the electrolyte, a cross-linked skeleton is constructed, and the aromatic triazine ring and carbonyl group are introduced to optimize the internal resistance of the battery.
It realizes low impedance, high safety composite electrolyte and safe semi-solid state battery, improving the overall performance and life of the battery.
Smart Images

Figure CN119050482B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a curing additive, a low-impedance composite electrolyte containing the curing additive, and a safe semi-solid battery. Background Art
[0002] As the world's pursuit of sustainable energy solutions continues to intensify and the demand for high-performance batteries such as portable electronic devices and electric vehicles continues to grow, the research and application of solid-state electrolytes has received unprecedented attention. The use of solid-state electrolytes provides higher safety standards and better electrochemical performance than traditional liquid electrolytes. This material not only prevents battery leakage and fire risks, but also extends the operating temperature range of the battery, thereby greatly improving the overall performance and life of the battery. Therefore, the development of solid-state electrolytes is not only the key to battery technology innovation, but also an important step in promoting the development of modern electronic technology.
[0003] However, while polymer monomers improve battery safety, they also bring some problems compared to traditional liquid batteries. Solid-state batteries that use polymer monomers as electrolytes abandon liquid organic electrolytes, which increases the difficulty of ion movement. At the same time, the solid-liquid interface replaced by the solid-solid interface further increases the interface impedance, resulting in serious high internal resistance problems in solid-state batteries, which limits the widespread promotion and use of solid-state batteries in practical applications.
[0004] Therefore, how to optimize the impedance of solid-state batteries while maintaining the safety of solid-state electrolytes has become a major difficulty in current research. It is very difficult to obtain a solid-state electrolyte that has both low impedance and high safety. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention constructs a cross-linked skeleton in the electrolyte to form a semi-solid electrolyte through the mutual compounding of a curing additive polymer monomer I and a polymer monomer II, and constructs an ion-conducting channel while reducing the internal resistance of the battery through the introduction of an aromatic triazine ring and a carbonyl group, thereby solving the problem of high safety but high impedance when preparing battery electrolytes using polymer monomers as raw materials, thereby obtaining a curing additive, a low-impedance composite electrolyte with low impedance and high safety, and a safe semi-solid battery using the electrolyte.
[0006] The present invention provides a curing additive, comprising a polymer monomer I and a polymer monomer II, wherein the polymer monomer I has the structural formula:
[0007]
[0008] Wherein, R1-R3 are selected from C1-C4 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C6 alkylene or haloalkyl, and R5 is selected from C1-C2 alkylene or haloalkyl;
[0009] The structural formula of the polymer monomer II is:
[0010]
[0011] Wherein, R6, R7, and R8 are selected from C1-C4 alkyl or halogenated alkyl.
[0012] The present invention also provides a low-impedance composite electrolyte, comprising a curing additive dispersed in a solvent.
[0013] The present invention also provides a highly safe semi-solid secondary battery, comprising a semi-solid electrolyte constructed of polymer monomers dispersed in a low-impedance composite electrolyte.
[0014] As some exemplary preferred schemes, in the structural formula of the polymer monomer I, the number of alkoxy groups in R1-R3 is less than 3, R1-R3 are selected from C1-C2 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C3 alkylene or halogenated hydrocarbon, R5 is selected from C1-C2 alkyl or haloalkyl, and in the structural formula of the polymer monomer II, R6, R7, and R8 are selected from C1-C2 alkylene or halogenated hydrocarbon.
[0015] As a further solution, the ratio of the polymer monomer I to the polymer monomer II is selected from 3:1 to 30:1.
[0016] As a further solution, the ratio of the polymer monomer I to the polymer monomer II is selected from a range of 6:1 to 15:1.
[0017] As a further solution, the mass content of the curing additive in the low-impedance composite electrolyte is 0.1%~8%.
[0018] As a further solution, the mass content of the curing additive in the low-impedance composite electrolyte is 1% to 6%.
[0019] As a further solution, the low-impedance composite electrolyte also includes a solvent, an additive, an inorganic electrolyte salt and an initiator.
[0020] As a further embodiment, the solvent is selected from one or more of carbonate compounds, carboxylate compounds, fluorinated compounds, ethers and epoxy compounds.
[0021] As a further embodiment, the carbonate compound is selected from any one or more of cyclic carbonate compounds and chain carbonate compounds.
[0022] As a further embodiment, the fluorinated compound is selected from any one or more of fluorinated carboxylic acid ester compounds, fluorinated ether compounds and fluorinated aromatic hydrocarbon compounds.
[0023] As a further solution, in the low-impedance composite electrolyte of the present invention, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.
[0024] As a further solution, in the low-impedance composite electrolyte of the present invention, the inorganic electrolyte salt is selected from at least one of borates, phosphates, sulfates, nitrates, antimonates, arsenates, and chlorates.
[0025] As a further embodiment, the inorganic electrolyte salt is substituted with fluorine.
[0026] As a further embodiment, the initiator is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.
[0027] The safe semi-solid battery also includes a positive electrode sheet, a negative electrode sheet and a separator.
[0028] As a further solution, the positive electrode sheet includes a positive electrode active material, a positive electrode binder, a positive electrode conductor, and a positive electrode current collector.
[0029] As a further solution, the positive electrode active material is selected from at least one of transition metal composite oxides and transition metal phosphate compounds.
[0030] As a further embodiment, the transition metal composite oxide has a general chemical formula selected from (A) x M1 1-p B1 p O2、r(A)2Mn 1-q B2 q O3·(1-r)AM2 1-s B3 s B3O2, (A) y (M3 2-h B4 h )2O4, 0.05≤x, 0≤p≤0.4, 0≤q≤0.4, 0≤s≤0.4, 0≤r≤1, y≤1.2, 0≤h≤0.8, wherein A is an active metal ion that can be deintercalated, specifically including any one or more of Li⁺, Na⁺, K⁺, Mg²⁺, Ca²⁺, M1, M2 、M3 is one or more transition metal elements, specifically including one or more of scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg); B1, B2, B3, B4 are doping elements, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).
[0031] As a further scheme, the chemical general formula of the transition metal phosphate compound is (C) z (M4 1-v B5 v )PO4, where 0 < z ≤ 1, 0 ≤ v ≤ 0.4, C represents a deintercalatable active metal ion, specifically including any one or several of Li⁺, Na⁺, K⁺, Mg²⁺, Ca²⁺; M4 represents one or more transition metal elements, specifically including one or more of scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg); B5 is a doping element, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).
[0032] As a further scheme, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0033] As a further scheme, the positive electrode conductive agent is selected from carbon materials, metal materials, or materials prepared by in-situ conductive curing.
[0034] As a further solution, the positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel, and copper.
[0035] As a further solution, the negative electrode sheet includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, and a negative electrode current collector.
[0036] As a further embodiment, the negative electrode active material has a coating on its surface, or may be mixed with another compound having a coating.
[0037] As a further solution, the coating is at least one of an oxide of the coating element, a hydroxide of the coating element, a hydroxyl oxide of the coating element, a carbonate or nitrate or phosphate or borate of the coating element, and a hydroxycarbonate of the coating element.
[0038] As a further embodiment, the coating element compound is amorphous or crystalline.
[0039] As a further solution, the separator is provided with at least one porous layer on its surface.
[0040] As yet a further aspect, the porous layer includes inorganic particles and a porous layer binder.
[0041] As a further solution, the thickness of the diaphragm layer is selected from 12 μm to 20 μm.
[0042] As a further solution, a safe semi-solid battery is prepared by the following method:
[0043] The battery is prepared by conventional methods. After the battery is formed, a low-impedance composite electrolyte is injected into the battery by a secondary liquid injection method, and polymerized and cured at 45°C to 75°C for 2h to 20h to obtain a safe semi-solid battery.
[0044] As a further solution, the battery prepared by the conventional method contains a single injection electrolyte.
[0045] As a further solution, the primary injection electrolyte can be understood as the electrolyte conventionally used in the prior art, and the present invention does not limit the type of the primary injection electrolyte.
[0046] As a further solution, for the purpose of convenient operation, the primary injection electrolyte can have the same type and content ratio of the solvent, additive, and inorganic electrolyte salt as those in the low-impedance composite electrolyte.
[0047] As a further solution, the mass ratio of the primary injection electrolyte to the low-impedance composite electrolyte is 1:0.24~1:0.35.
[0048] As a further solution, the curing temperature is selected from 50°C to 70°C, and the curing time is selected from 3h to 10h.
[0049] Compared with the prior art, the present invention has at least the following beneficial effects:
[0050] The low-impedance composite electrolyte and safe semi-solid battery provided by the present invention introduce polymer monomers I and II into the electrolyte, and use polymer monomers I and II to construct a uniform, stable, and anti-swelling three-dimensional network structure. At the same time, adjacent -C=C and -COO- groups in the polymer monomer I are used to optimize the crosslinking and activation sites, and avoid the occurrence of side reactions. On this basis, -Si-O is further introduced to reduce the HF content, and the stability and flexibility of the electrolyte are further improved. The introduction of carbonyl and triazine rings in the polymer monomer II further reduces the battery impedance, and solves the high impedance problem of the battery when the polymer monomer is used as the electrolyte material.
[0051] In the present invention, the safe semi-solid-state battery containing a low-impedance composite electrolyte exhibits excellent safety, has an ultra-high pass rate in a 10-hour overcharge test, and has a low explosion pressure; on this basis, the presence of the low-impedance composite electrolyte inhibits the expansion of the battery, and while improving the battery cycle performance, the unique polymer monomer structure gives the safe semi-solid-state battery an ultra-low impedance, thereby obtaining a low-impedance composite electrolyte and a safe semi-solid-state battery with both high safety and electrochemical capabilities. DETAILED DESCRIPTION
[0052] For ease of understanding, the battery electrolyte of the present invention will be described in more detail below, and examples of the present invention will be given, but the scope of the present invention is not limited thereby.
[0053] The present invention provides a safe semi-solid battery, comprising a semi-solid electrolyte constructed by polymer monomers dispersed in a low-impedance composite electrolyte, wherein the polymer monomers include polymer monomers I and polymer monomers II, and the structural formula of polymer monomer I is:
[0054]
[0055] Wherein, R1-R3 are selected from C1-C4 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C6 alkylene or haloalkyl, and R5 is selected from C1-C2 alkyl or haloalkyl;
[0056] The structural formula of the polymer monomer II is
[0057]
[0058] Wherein, R6, R7, and R8 are selected from C1-C4 alkylene groups or halogenated hydrocarbon groups.
[0059] In the development of low-impedance composite electrolytes for safe semi-solid batteries, by introducing adjacent -C=C and -COO- groups into polymer monomers I and II, the ion conductivity of the battery is further improved on the basis of cross-linking and curing of the electrolyte, and the internal impedance is effectively reduced, and the decomposition and side reactions of the electrolyte are reduced. In addition, the introduction of adjacent -C=C and -COO- groups also optimizes the cross-linking structure and active sites, thereby further enhancing the electrochemical performance of the battery. In polymer monomer I, the further introduction of -Si-O groups can not only effectively improve the ion conductivity, but also help to reduce the HF content and enhance the stability and flexibility of the electrolyte after curing. For polymer monomer II, the introduction of carbonyl groups based on adjacent -C=C and -COO- can effectively identify and guide the transport and transportation of ions, and construct an efficient ion transport channel that is limited to ions. On this basis, the presence of localized π-electron-rich aromatic triazine rings helps to inhibit the formation of interfacial phases and reduce low interfacial impedance, thereby significantly reducing internal resistance.
[0060] In the present invention, we propose a polymer monomer I containing -C=C, -Si-O and -COO- groups at the same time. The coexistence of the three functional groups in the polymer monomer I is conducive to optimizing the cross-linking site to the greatest extent and improving the compounding effect between the three. In addition, the design of the monomer I effectively avoids the side reactions that may be generated between different substances due to the dispersion of functional groups, thereby further improving the safety performance of the safe semi-solid battery. Based on the curing monomer I, we further introduce the polymer monomer II, and through the compounding of the two, not only the reaction activity is improved, but also a stable, uniform and anti-expansion three-dimensional network structure is further constructed. In addition, on the basis of the -C=C, -Si-O and -COO- groups, carbonyl and triazine rings are further introduced, which greatly reduces the impedance of the safe semi-solid battery, and obtains a safe semi-solid battery with high safety and low resistance.
[0061] According to the safe semi-solid battery containing a low-impedance composite electrolyte, the present invention also proposes a low-impedance composite electrolyte, including polymer monomer I and polymer monomer II for in-situ construction of a semi-solid electrolyte.
[0062] According to the low-impedance composite electrolyte, the present invention also proposes a curing additive, polymer monomer I and polymer monomer II.
[0063] As some exemplary preferred schemes, in the structural formula of the polymer monomer I, the number of alkoxy groups in R1-R3 is less than 3, R1-R3 are selected from C1-C2 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C3 alkylene or halogenated hydrocarbon, R5 is selected from C1-C2 alkyl or haloalkyl, and in the structural formula of the polymer monomer II, R6, R7, and R8 are selected from C1-C2 alkylene or halogenated hydrocarbon.
[0064] As a further embodiment, the present invention also provides a polymer monomer I selected from One of the above, polymer monomer II is selected from tris(2-acryloyloxyethyl)isocyanurate.
[0065] As a further solution, the ratio of polymer monomer I to polymer monomer II is selected from 3:1 to 30:1; when the ratio of polymer monomer I to polymer monomer II is greater than 30:1, the high polymer monomer I may lead to insufficient three-dimensional network structure, making it difficult for the battery to suppress the expansion phenomenon during the cycle, and reducing the battery cycle stability performance; and when the ratio of polymer monomer I to polymer monomer II is lower than 6:1, although the integrity of the three-dimensional network structure is improved, the battery is affected by the capacity retention rate and rate performance of the normal temperature cycle due to the decrease in the content of polymer monomer I and the increase in impedance. Therefore, it is very important to ensure that the ratio of polymer monomer I to polymer monomer II is reasonable, so as to ensure that the battery has good expansion suppression ability and long-term cycle stability, and to take into account the optimization of the battery electrochemical performance.
[0066] As a further solution, in order to take into account the battery rate performance, cycle performance and safety during use, the ratio of polymer monomer I to polymer monomer II is preferably in the range of 6:1~15:1. When the ratio of polymer monomer I to polymer monomer II is selected from 6:1~15:1, the compounding effect of polymer monomer I and polymer monomer II can be maximized, which can not only construct a stable and uniform three-dimensional network framework, but also help to further improve the network cross-linking sites, optimize the ion transmission path, and reduce the internal resistance. When the ratio of polymer monomer I to polymer monomer II is preferably in the range of 6:1~15:1, we obtained a safe semi-solid battery with high cycle capacity, high safety and low resistance.
[0067] As a further solution, the mass content of the curing additive in the low-impedance composite electrolyte is 0.1%~8%; the mass content of the curing additive in the low-impedance composite electrolyte is very important. When the mass content of the curing additive is higher than 8%, excessive curing additive will lead to excessive cross-linking of the three-dimensional framework, which may extend the ion transmission path and complicate the transmission path on the one hand, and may also increase the interface resistance and affect the electrochemical performance of the battery on the other hand; when the mass content of the curing additive is lower than 0.1%, too low a content of the curing additive may not be able to achieve the construction of the three-dimensional framework, making it difficult for the battery to suppress the expansion phenomenon during the cycle, resulting in poor cycle performance and safety performance. At the same time, too low a content of the curing additive cannot contribute to the ion conductivity, thus affecting the electrochemical performance of the battery. Therefore, in order to further improve the electrochemical performance and safety performance of the battery, we must find a reasonable content balance while maintaining the electrolyte performance and battery efficiency.
[0068] As a further solution, the content of the curing additive in the low-impedance composite electrolyte is optimized. The mass content of the curing additive in the low-impedance composite electrolyte is preferably 1%~6%. When the content is 0.1%~8%, the increase in the content of the curing additive is accompanied by the gradual stabilization and uniformity of the three-dimensional framework, so that the battery volume stability is simultaneously improved and the explosion pressure is gradually reduced. At the same time, the increase in the content of the curing additive is also helpful to optimize the interface impedance and improve the electrochemical performance of the battery; when the content of the curing additive is controlled within 1%~6%, a safe semi-solid battery with balanced safety and rate performance can be obtained. When it is higher than 6%, the interface impedance may increase, and when it is lower than 1%, a three-dimensional framework with higher stability and ion conductivity cannot be obtained. Therefore, the mass content of the curing additive in the low-impedance composite electrolyte is preferably 1%~6%.
[0069] As a further solution, the low-impedance composite electrolyte also includes a solvent, an additive, an inorganic electrolyte salt and an initiator.
[0070] As a further embodiment, the solvent is selected from one or more of carbonate compounds, carboxylate compounds, fluorinated compounds, ethers and epoxy compounds.
[0071] As a further embodiment, the carbonate compound is selected from any one or more of cyclic carbonate compounds and chain carbonate compounds.
[0072] As a further embodiment, the cyclic carbonate compound is selected from any one or more of ethyl carbonate, ethylene carbonate, propylene carbonate, methyl vinyl carbonate, fluoroethylene carbonate, vinyl chloride carbonate, vinylene carbonate, vinyl ethylene carbonate, methylene vinyl carbonate, fluoroethylene carbonate, trifluoromethyl vinyl carbonate, and difluoroethylene carbonate.
[0073] As a further embodiment, the chain carbonate compound is selected from any one or more of dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and ethyl methyl carbonate.
[0074] As a further embodiment, the carboxylate compound is selected from any one or more of ethyl propionate, propyl propionate, ethyl butyrate, propyl acetate, butyl acetate, methyl acetate and ethyl acetate.
[0075] As a further embodiment, the fluorinated compound is selected from any one or more of fluorinated carboxylic acid ester compounds, fluorinated ether compounds and fluorinated aromatic hydrocarbon compounds.
[0076] As a further embodiment, the fluorinated carboxylic acid ester compound is selected from any one or more of ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, ethyl trifluoropropionate, methyl trifluoropropionate, ethyl tetrafluoroacetate, methyl trifluoroacetate, and ethyl difluoropropionate.
[0077] As a further embodiment, the fluorinated ether compound is selected from any one or more of fluoroether, methyl (2,2,2-trifluoroethoxy) ethyl ether, trifluoroethyl (2,2,2-trifluoroethoxy) ethyl ether, trifluoromethyl (2,2,2-trifluoroethoxy) ethyl ether, fluorobis (trifluoromethyl) oxyethane, 2-(2,2,2-trifluoroethoxy)-1,1,1-trifluoroethane, fluorotriethyl ether, perfluoro-2-butoxyethanol, and pentafluoro-1-propyl ethyl ether.
[0078] As a further embodiment, the fluorinated aromatic compound is selected from any one or more of fluorobenzene, difluorobenzene, trifluorobenzene, perfluoromethylbenzene, tetrafluorobenzene, pentafluorobenzene, perfluorobenzene, fluorotoluene and fluoroterphenyl.
[0079] As a further embodiment, the ether compound is selected from any one or more of 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, dimethoxymethane, 1,2-dimethoxypropane, diethoxymethane, polyoxyethylene dimethyl ether, methoxypropoxypropane, and ethylene glycol dimethyl ether.
[0080] As a further embodiment, the epoxy compound is selected from any one or more of ethylene oxide, propylene oxide, butylene oxide, cyclohexene oxide, benzene oxide, 1,2-epoxyheptane, 1,2-epoxyoctane, 1,3-dioxolane, 1,3-dioxane, and 1,4-dioxane.
[0081] As a further solution, in the low-impedance composite electrolyte of the present invention, the additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.
[0082] As a further embodiment, the lithium salt compound is selected from at least one of lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, lithium hexafluorophosphate, lithium difluorosulfonyl imide, lithium bis(trifluoromethanesulfonyl)imide, lithium fluoride, and lithium chloride.
[0083] As a further embodiment, the nitrile compound is at least one selected from the group consisting of adiponitrile, succinonitrile, hexanetrinitrile, propionitrile, benzonitrile, acetonitrile and isobutyronitrile.
[0084] As a further embodiment, the organosilicon compound is at least one selected from tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(trimethylsilyl)borate, polydimethylsiloxane, and trimethylchlorosilane.
[0085] As a further embodiment, the sultone compound is selected from at least one of 1,3-propane sultone, 1,3-propylene sultone, benzene sultone, cyclohexene sultone, cyclopentene sultone, vinyl sultone, octyl sultone and phenyl sultone.
[0086] As a further embodiment, the sulfate ester compound is selected from at least one of vinyl sulfate, dimethyl sulfate, ethyl sulfate, propylene sulfate, dimethoxyethane sulfate, and methoxysulfate.
[0087] As a further solution, in the low-impedance composite electrolyte of the present invention, the inorganic electrolyte salt is selected from at least one of borates, phosphates, sulfates, nitrates, antimonates, arsenates, and chlorates.
[0088] As a further embodiment, the inorganic electrolyte salt is substituted with fluorine.
[0089] As a further embodiment, the inorganic electrolyte salt is selected from LiPF6 and NaPF6.
[0090] As a further embodiment, the initiator is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.
[0091] The safe semi-solid battery also includes a positive electrode sheet, a negative electrode sheet and a separator.
[0092] As a further solution, the positive electrode sheet includes a positive electrode active material, a positive electrode binder, a positive electrode conductor, and a positive electrode current collector.
[0093] As a further solution, the positive electrode active material is selected from at least one of transition metal composite oxides and transition metal phosphate compounds.
[0094] As a further embodiment, the transition metal composite oxide has a general chemical formula selected from (A) x M1 1-p B1 p O2、r(A)2Mn 1-q B2 q O3·(1-r)AM2 1-s B3 s B3O2, (A) y (M3 2-h B4 h )2O4, 0.05≤x, 0≤p≤0.4, 0≤q≤0.4, 0≤s≤0.4, 0≤r≤1, y≤1.2, 0≤h≤0.8, wherein A is an active metal ion that can be deintercalated, specifically including any one or more of Li⁺, Na⁺, K⁺, Mg²⁺, Ca²⁺, M1, M2 、 M3 is one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum B1, B2, B3, and B4 are doping elements, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).
[0095] As a further embodiment, the chemical formula of the transition metal phosphate compound is (C) z (M4 1-v B5 v)PO4, 0 < z ≤ 1, 0 ≤ v ≤ 0.4, C represents an activatable metal ion that can be deintercalated, specifically including any one or more of Li⁺, Na⁺, K⁺, Mg²⁺, Ca²⁺, M4 represents one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg), and B5 is a doping element, specifically including any one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).
[0096] As a further embodiment, the cathode binder is selected from at least one of thermoplastic resins, acrylic resins, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0097] As a further embodiment, the thermoplastic resin includes at least one of polyvinylidene fluoride, polyvinyl fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride - hexafluoropropylene, copolymers of tetrafluoroethylene - hexafluoropropylene, copolymers of tetrafluoroethylene - perfluoroalkyl vinyl ether, copolymers of ethylene - tetrafluoroethylene, copolymers of vinylidene fluoride - tetrafluoroethylene, copolymers of vinylidene fluoride - trifluoroethylene, copolymers of vinylidene fluoride - trichloroethylene, copolymers of vinylidene fluoride - fluoroethylene, copolymers of vinylidene fluoride - hexafluoropropylene - tetrafluoroethylene, thermoplastic polyimide, polyethylene, and polypropylene.
[0098] As a further embodiment, the acrylic resin includes at least one of acrylic vinyl ester resin, acrylic methyl ester resin, acrylic butyl ester resin, acrylic styrene resin, acrylate resin, acrylate copolymer resin, acrylic resin, and acrylic emulsion resin.
[0099] As a further embodiment, the cathode conductive agent is selected from carbon materials, metal materials, or materials prepared by in-situ conductive curing.
[0100] As a further embodiment, the carbon material is selected from any one of carbon nanotubes, graphite, graphene, carbon fiber, activated carbon, and Super P.
[0101] As a further solution, the metal material is selected from a single substance or oxide of any one element selected from silver, copper, nickel, cobalt, aluminum, titanium, rhodium and gold.
[0102] As a further solution, the positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel and copper.
[0103] As a further solution, the negative electrode sheet includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, and a negative electrode current collector.
[0104] As a further embodiment, the negative electrode active material is selected from at least one of natural graphite, artificial graphite, intermediate phase microcarbon beads, hard carbon, soft carbon, silicon (oxygen), silicon (oxygen)-carbon composites, alloy compounds, Sn, SnO, and SnO2.
[0105] As a further embodiment, the negative electrode active material has a coating on its surface, or may be mixed with another compound having a coating.
[0106] As a further solution, the coating is at least one of an oxide of the coating element, a hydroxide of the coating element, a hydroxyl oxide of the coating element, a carbonate or nitrate or phosphate or borate of the coating element, and a hydroxycarbonate of the coating element.
[0107] As a further embodiment, the coating element compound is amorphous or crystalline.
[0108] In a further embodiment, the coating element is any one or more of magnesium (Mg), aluminum (Al), cobalt (Co), K, Na, calcium (Ca), silicon (Si), titanium (Ti), vanadium (V), tin (Sn), germanium (Ge), gallium (Ga), boron (B), arsenic (As), zirconium (Zr), tantalum (Ta), niobium (Nb), and lanthanum (La).
[0109] As a further solution, the type of the negative electrode binder is not limited, and technicians can choose according to actual needs, including at least one of styrene-butadiene rubber, styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, sodium carboxymethyl cellulose, and polyacrylate.
[0110] As a further solution, the type of the negative electrode conductive agent is not limited, and technicians can choose according to actual needs, including at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, multi-arm carbon nanotubes, single-walled carbon nanotubes, graphene, conductive carbon black and carbon nanofibers.
[0111] As a further solution, the negative electrode current collector is selected from metal materials, including any one metal foil layer of copper, aluminum, nickel, and tin.
[0112] As a further solution, the isolation film is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide and aramid.
[0113] As a further solution, the separator is provided with at least one porous layer on its surface.
[0114] As yet a further aspect, the porous layer includes inorganic particles and a porous layer binder.
[0115] As a further embodiment, the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.
[0116] As a further embodiment, the porous layer is selected from at least one of polyvinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, carboxymethyl cellulose sodium, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0117] As a further solution, the thickness of the diaphragm layer is selected from 12 μm to 20 μm.
[0118] As a further solution, a safe semi-solid battery is prepared by the following method:
[0119] The battery is prepared by conventional methods. After the battery is formed, a low-impedance composite electrolyte is injected into the battery by a secondary liquid injection method, and polymerized and cured at 45°C to 75°C for 2h to 20h to obtain a safe semi-solid battery.
[0120] Through the secondary injection method, we effectively avoided the adverse effects of subsequent operations of the initial injection on the low-impedance composite electrolyte; and achieved control of key parameters in the polymerization and curing process, thereby ensuring that the electrolyte is cured under the most optimized conditions, improving the consistency and repeatability of battery performance.
[0121] As a further solution, the battery prepared by the conventional method contains a single injection electrolyte.
[0122] As a further solution, the primary injection electrolyte can be understood as the electrolyte conventionally used in the prior art, and the present invention does not limit the type of the primary injection electrolyte.
[0123] As a further solution, for the purpose of convenient operation, the primary injection electrolyte can have the same type and content ratio of the solvent, additive, and inorganic electrolyte salt as those in the low-impedance composite electrolyte.
[0124] As a further solution, the mass ratio of the primary injection electrolyte to the low-impedance composite electrolyte is 1:0.24~1:0.35.
[0125] As a further solution, the curing temperature is selected from 50°C~70°C, and the curing time is selected from 3h~10h; higher curing temperature and longer curing time can optimize the in-situ curing effect and obtain a more stable and safe semi-solid battery. Therefore, with the gradual increase of time and temperature, the capacity retention rate of 200 cycles at room temperature gradually increases, the explosion pressure gradually decreases, and the safety gradually improves. However, while the temperature increases the cross-linking degree of the polymer monomer, the rate performance and battery impedance are affected, showing slight volatility. Therefore, in order to ensure the optimal balance of battery performance, the preferred curing temperature is 50°C~70°C, and the preferred curing time is 3h~10h.
[0126] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0127] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.
[0128] Example 1
[0129] Preparation of safe lithium-ion semi-solid-state batteries
[0130] The positive electrode active material lithium cobalt oxide, the conductive agent Super P, polyvinylidene fluoride, and carbon nanotubes were mixed in a weight ratio of 95:2:2.5:0.5, N-methylpyrrolidone was added, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry was 70wt%. The obtained positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and the aluminum foil coated with the positive electrode slurry was dried at 90°C, and then cold pressed, cut, and slit to obtain a positive electrode sheet.
[0131] The negative electrode active materials graphite, silicon (oxygen), carboxymethyl cellulose, binder styrene butadiene rubber, polyacrylate, multi-arm carbon nanotubes, and single-wall carbon nanotubes are mixed in a weight ratio of 85.5:10:0.6:1.3:2:0.5:0.1, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried at 80°C, and then cold pressed, cut, and slit to obtain the negative electrode sheet.
[0132] In a dry argon atmosphere glove box, EC / EMC (1:9, wt.) solvent, 0.5% vinyl sulfate, and 8% fluoroethylene carbonate were dissolved and stirred thoroughly, and then 1.1M LiPF6 was added and mixed evenly to obtain a primary injection electrolyte. 20% of the electrolyte was mixed evenly with polymer monomers and ammonium persulfate to obtain a low-impedance composite electrolyte (polymer monomers, addition amounts and types are shown in Table 1).
[0133] The separator is a 16 μm thick polyethylene separator.
[0134] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation. After welding the pole ears, they are placed in the outer packaging foil aluminum-plastic film, dried, and injected with a primary injection electrolyte. After vacuum packaging, standing, and formation, a low-impedance composite electrolyte is added. After sufficient standing, it is heated and polymerized (the heating temperature and polymerization time are shown in Table 1), and a safe semi-solid battery is obtained after a capacity test.
[0135] Example 2-15
[0136] Some parameters in Example 1 were changed, and the rest of the parameters were prepared in the same manner as in Example 1. The parameter changes are shown in Table 1.
[0137] Example 16 Preparation of sodium ion safe semi-solid battery
[0138] Will Na 0.44 MnO2, conductive agent Super P, polyvinylidene fluoride, and carbon nanotubes were mixed in a weight ratio of 95:2:2.5:0.5, and N-methylpyrrolidone was added to prepare a positive electrode slurry and coated on the positive electrode current collector aluminum foil. The aluminum foil coated with the positive electrode slurry was heated at 90 o C, and then cold pressed, cut into pieces, and slit to obtain the positive electrode sheet.
[0139] The negative electrode active material hard carbon, carboxymethyl cellulose, binder styrene butadiene rubber, polyacrylate, multi-arm carbon nanotubes, and single-wall carbon nanotubes were mixed in a weight ratio of 85.5:0.6:1.3:2:0.5:0.1, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil; the copper foil was heated at 80 o C, and then cold pressed, cut and slit to obtain the negative electrode sheet.
[0140] In a dry argon atmosphere glove box, EC / EMC (1:9, wt.) solvent, 0.5% vinyl sulfate, and 8% fluoroethylene carbonate were dissolved and stirred thoroughly, and then 1.1M NaPF6 was added and mixed evenly to obtain a primary injection electrolyte. 20% of the electrolyte was mixed evenly with polymer monomers and ammonium persulfate to obtain a low-impedance composite electrolyte (polymer monomers, addition amounts and types are shown in Table 1).
[0141] The separator is a 16 μm thick polyethylene separator.
[0142] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation. After welding the pole ears, they are placed in the outer packaging foil aluminum-plastic film, dried, and injected with a primary injection electrolyte. After vacuum packaging, standing, and formation, a low-impedance composite electrolyte is added. After sufficient standing, it is heated and polymerized (the heating temperature and polymerization time are shown in Table 1), and a safe semi-solid battery is obtained after a capacity test.
[0143] Comparative Examples 1-6, 8
[0144] Some parameters in Comparative Examples 1-6 and 8 were changed, and the rest of the parameters were prepared in the same manner as in Example 1. The parameter changes are shown in Table 1.
[0145] Comparative Example 7
[0146] The preparation is carried out in the same manner as in Example 1, except that the low-impedance composite electrolyte is injected at the same time as the primary injection electrolyte.
[0147] Comparative Example 9
[0148] Some parameters in Example 16 were changed, and the rest of the parameters were prepared in the same manner as in Example 16. The parameter changes are shown in Table 1.
[0149] Test method:
[0150] (1) Lithium / sodium ion battery cycle performance test
[0151] Place the battery at 25 o C constant temperature box for 2 hours to reach a constant temperature. The battery that has reached a constant temperature is heated at 0.5C (25 o C) Charge at a constant current until the voltage is 4.45V (lithium battery) or 4V (sodium battery), then discharge at a constant current of 0.5C until the voltage is 3V (lithium battery) or 1.5V (sodium battery). This is one cycle, and the discharge capacity is recorded. Cycle capacity retention rate = discharge capacity of the nth cycle / discharge capacity of the first cycle * 100%. The discharge capacity of the first cycle is recorded as C0.
[0152] (2) Battery rate performance test
[0153] After the battery cell is fully charged, it is discharged at a 2C rate to obtain the discharge capacity C1, C1 / C0=(C1-C0) / C0*100%.
[0154] (3) Battery impedance test
[0155] At 25°C, after fully charging the battery cell, use a BK-300A battery internal resistance tester to clamp the two tabs of the battery cell, and the reading is the internal resistance.
[0156] (4) Overcharge test
[0157] The battery is charged to 6V at 1C and then maintained for 10 hours. If the battery does not catch fire or explode, the test is considered to have passed. Ten parallel samples are tested for each formulation. The overcharge test pass rate = the number of batteries that passed the test / 10.
[0158] (5) Explosion pressure test
[0159] Under full charge conditions, in a closed furnace chamber, heat the battery until it explodes, and test the gas pressure in the furnace chamber at the time of explosion.
[0160] Test Results
[0161] The test results of Examples 1-16 and Comparative Examples 1-9 are shown in Table 2.
[0162] Table 1
[0163]
[0164] Note: polymer monomer 1 is of formula I-2, polymer monomer 2 is of formula I-6, polymer monomer 3 is of formula I-8, polymer monomer 4 is of formula I-5; polymer monomer 5 is tris(2-acryloyloxyethyl)isocyanurate, polymer monomer 6 is allyl-2-cyanoacrylate, polymer monomer 7 is butadiene, polymer monomer 8 is polymethyl methacrylate, and polymer monomer 9 is polydimethylsiloxane.
[0165] Table 2
[0166]
[0167] Examples 1-16 as a whole show better capacity retention rate after 200 cycles at room temperature, 2C capacity retention rate and safer explosion pressure than Comparative Examples 1-9.
[0168] From the comparison of Examples 1 and 16 and Comparative Examples 1 and 9, it can be seen that the addition of polymer monomer I and polymer monomer II significantly enhances the electrochemical performance and cycle stability of lithium ion safety semi-solid batteries and sodium ion safety semi-solid batteries. This may be because polymer monomer I having -C=C, -Si-O and -COO- groups and polymer monomer II having -C=C, -COO-, carbonyl and triazine rings can effectively improve the three-dimensional cross-linked structure of the solid electrolyte, improve the flexibility of the cross-linked structure, reduce battery impedance, inhibit side reactions such as redox, reduce HF content, and reduce decomposition of the electrolyte, thereby obtaining a safe semi-solid battery with high electrochemical capability and high safety.
[0169] It can be observed from Example 2, Comparative Examples 2 and 3 that the simultaneous presence of -C=C, -Si-O and -COO- functional groups is very important for improving the electrochemical capacity and safety of the safe semi-solid-state battery. Under the same test conditions, Comparative Example 2 containing only -C=C and Comparative Example 3 without -Si-O both exhibited worse cycle capacity, capacity retention rate and safety than Example 2. This may be because the combination of -C=C, -Si-O and -COO- is of great significance for improving the electrochemical capacity of the performance of the safe semi-solid-state battery and reducing the explosion pressure.
[0170] While Example 2 and Comparative Example 4 show another situation. In Comparative Example 4, -C=C, -Si-O and -COO- are respectively located on different monomer polymers. When the cycle capacity retention rate and 2C capacity retention rate are tested, Comparative Example 4 shows a performance far lower than that of Example 2. Similarly, the explosion pressure is also far higher than that of Example 2. This may be because, in polymer monomer I, -C=C and -COO- in the ortho position can effectively optimize the three-dimensional framework cross-linking structure, optimize the active sites, and improve the ion conductivity. Furthermore, when -C=C, -Si-O and -COO- are located in the same monomer polymer, not only the ion conductivity is further improved, but also harmful side reactions between multiple monomer polymers are avoided, thereby improving the battery stability and safety performance.
[0171] Comparative Examples 5 and 6 show the situation when polymer monomer I and polymer monomer II are added separately. From Example 2, Comparative Examples 5 and 6, it can be seen that the compounding effect between polymer monomer I and polymer monomer II is particularly important for improving the electrochemical performance and safety performance of the battery. When only polymer monomer I is present (Comparative Example 5), the three-dimensional cross-linked skeleton formed by polymer monomer I may not be uniform and complete enough, and it is difficult to inhibit battery expansion and improve cycle performance. Therefore, Comparative Example 5 shows significantly lower electrochemical performance and safety than Example 2; when only polymer monomer II is added (Comparative Example 6), due to the lack of doping of polymer monomer I, the pressure of Comparative Example 6 at the time of explosion is slightly better than that of Comparative Example 5, but it is still far lower than that of Example 2. At the same time, the electrochemical performance is also significantly lower. This phenomenon shows that the use of polymer monomer II alone cannot meet our comprehensive requirements for battery performance. Therefore, the reasonable compounding of polymer monomers I and II is not only the key to improving battery performance, but also provides a new method and idea for the development of efficient and safe energy storage devices. Through reasonable compounding, while synergistically improving the electrochemical performance of the battery, the internal network structure is optimized, the electrochemical performance and stability are improved, the battery impedance and explosion pressure are reduced, and the safety performance is improved.
[0172] Example 2 and Comparative Example 8 demonstrate the effect of polymer monomer II. Compared with Comparative Example 8, Example 2 exhibits an impedance far superior to that of Comparative Example 8. This is because the introduction of the carbonyl group can effectively construct an efficient ion transport channel that only allows ions to pass through, promote the formation of a stable interface layer, and reduce the interface impedance. On this basis, the presence of the π-electron-rich aromatic triazine ring significantly reduces the internal impedance, thereby obtaining a safe semi-solid-state battery with high safety and low impedance.
[0173] Different injection methods will also affect the electrochemical capacity and safety of safe semi-solid batteries. By comparing Example 2 and Comparative Example 7, it can be seen that when the single injection method is used, Comparative Example 7 shows a capacity retention rate of 200 cycles at room temperature and a 2C battery rate that are much lower than those of Example 2. At the same time, the explosion pressure is much higher than that of Example 2. This is because after the first injection of the battery is completed, the low-impedance composite electrolyte in the battery may be affected by subsequent operating steps, while the low-impedance composite electrolyte contained in the battery prepared by the secondary injection method effectively avoids these problems. Therefore, choosing the secondary injection method is conducive to improving the consistency and repeatability of the battery development process, and improving the electrochemical performance and safety.
[0174] By comparing Example 2 with Example 13, it can be observed that, within the structural formula range of the in-situ curing monomer I and the in-situ curing monomer II, as the content of the siloxane group gradually decreases, the cycle capacity retention rate of Example 2 shows a certain improvement; and by comparing the results of Example 13 with Example 14, it can be found that when the length of the carbon chain in the silane is shortened, the explosion pressure is optimized, indicating that the short carbon chain silane group can effectively improve the safety of the battery; in addition, by observing Example 2 and Example 15, it can be found that reducing the number of carbon atoms between the siloxane group and the carboxylate group can optimize the explosion pressure to a certain extent.
[0175] The ratio of polymer monomer I to polymer monomer II is also one of the factors affecting the cycle stability and safety of the safe semi-solid-state battery. From the comparison of Examples 2, 8, and 9, it can be seen that when the mass ratio of polymer monomer I to polymer monomer II is in the range of 6:1 to 15:1, it is conducive to obtaining a safe semi-solid-state battery with uniform and stable structure, low impedance, excellent cycle life, and good safety performance. Therefore, according to Examples 2, 8, and 9, the preferred ratio of polymer monomer I to polymer monomer II is 6:1 to 15:1.
[0176] By comparing Examples 2 and 10-12, it can be observed that when the mass content of the curing additive in the low-impedance composite electrolyte is 0.1%-8%, as the total content of the polymer monomer gradually increases, the capacity retention rate after 200 cycles at room temperature shows an upward trend to a certain extent, and the explosion pressure is also optimized. This may be because the increase in the content of the polymer monomer in the low-impedance composite electrolyte helps to build a more stable solid electrolyte, but it may also cause a slight decrease in the 2C rate. Therefore, considering the changes in the electrochemical performance and safety of the battery, according to Examples 2 and 10-12, the total content of the polymer monomer in the low-impedance composite electrolyte is preferably 1%~6%.
[0177] It can be observed from Examples 1-7 that both curing time and temperature will affect the curing of polymer monomers in the low-impedance composite electrolyte; under the reaction conditions of 45°C~75°C and 2h~20h, higher curing temperatures and longer curing times can optimize the in-situ curing effect and obtain a more stable and safe semi-solid battery. As time and temperature gradually increase, the capacity retention rate after 200 cycles at room temperature gradually increases, the explosion pressure decreases, and the safety gradually increases; however, although the increase in temperature increases the cross-linking degree of the polymer monomer, it also has a certain impact on the rate performance and impedance. Therefore, in order to ensure the best balance of battery performance, according to Examples 1-7, the curing temperature is selected to be 50°C~70°C and the curing time is 3h~10h.
[0178] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A low impedance composite electrolyte, characterized in that: It includes a curing additive, wherein the curing additive includes a polymer monomer I and a polymer monomer II, and the polymer monomer I has a structural formula of: ; wherein R1-R3 are selected from C1-C4 alkyl, alkoxy, haloalkyl or haloalkoxy, R4 is selected from C1-C6 alkylene or haloalkyl, R5 is selected from C1-C2 alkyl or haloalkyl, and polymer monomer I has a -Si-O group; The structural formula of the polymer monomer II is ; Among them, R6, R7, and R8 are selected from C1-C4 alkylene groups or halogenated hydrocarbon groups, the mass content of the curing additive in the low-impedance composite electrolyte is 0.1%~8%, and the ratio of polymer monomer I to polymer monomer II is selected from 6:1~15:
1.
2. The low-impedance composite electrolyte according to claim 1, characterized in that: In the structural formula of the polymer monomer I, the number of alkoxy groups in R1-R3 is less than 3, R1-R3 are selected from C1-C2 alkyl, alkoxy, halogenated alkyl or halogenated alkoxy, R4 is selected from C1-C3 alkylene or halogenated hydrocarbon group, R5 is selected from C1-C2 alkyl or halogenated alkyl group, and R6, R7, and R8 are selected from C1-C2 alkylene or halogenated hydrocarbon group in the structural formula of the polymer monomer II.
3. The low-impedance composite electrolyte according to claim 1, characterized in that: The content of the curing additive in the low-impedance composite electrolyte is 1% to 6%.
4. The low-impedance composite electrolyte according to claim 1, characterized in that: The low-impedance composite electrolyte also includes a solvent, an additive, an inorganic electrolyte salt and an initiator.
5. The low-impedance composite electrolyte according to claim 4, characterized in that: The solvent is selected from one or more of carbonate compounds, carboxylate compounds, fluorinated compounds, ethers and epoxy compounds.
6. The low-impedance composite electrolyte according to claim 5, characterized in that: The carbonate compound is selected from any one or more of cyclic carbonate compounds and chain carbonate compounds.
7. The low-impedance composite electrolyte according to claim 5, characterized in that: The fluorinated compound is selected from any one or more of fluorinated carboxylic acid ester compounds, fluorinated ether compounds and fluorinated aromatic hydrocarbon compounds.
8. The low-impedance composite electrolyte according to claim 4, characterized in that: The additive is selected from at least one of lithium salt compounds, nitrile compounds, organosilicon compounds, sultone compounds, and sulfate compounds.
9. The low-impedance composite electrolyte according to claim 4, characterized in that: The inorganic electrolyte salt is selected from at least one of borates, phosphates, sulfates, nitrates, antimonates, arsenates and chlorates.
10. The low-impedance composite electrolyte according to claim 4, characterized in that: The inorganic electrolyte salt is substituted with fluorine.
11. The low-impedance composite electrolyte according to claim 4, characterized in that: The initiator is selected from one or more of ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.
12. A safe semi-solid battery, characterized in that: An electrolyte comprising the low-impedance composite electrolyte described in any one of claims 1-11.
13. The safe semi-solid battery according to claim 12, characterized in that: The safe semi-solid battery also includes a positive electrode sheet, a negative electrode sheet and a separator.
14. The safe semi-solid battery according to claim 13, characterized in that: The positive electrode sheet comprises a positive electrode active material, a positive electrode binder, a positive electrode conductor, and a positive electrode current collector.
15. The safe semi-solid battery according to claim 14, characterized in that: The positive electrode active material is selected from at least one of transition metal composite oxides and transition metal phosphate compounds.
16. The safe semi-solid battery according to claim 15, characterized in that: The transition metal composite oxide chemical formula is selected from (A) x M1 1-p B1 p O2、r(A)2Mn 1-q B2 q O3·(1-r)AM2 1-s B3 s B3O2, (A) y (M3 2-h B4 h )2O4, 0.05≤x, 0≤p≤0.4, 0≤q≤0.4, 0≤s≤0.4, 0≤r≤1, y≤1.2, 0≤h≤0.8, wherein A is an active metal ion that can be deintercalated, specifically including any one or more of Li⁺, Na⁺, K⁺, Mg²⁺, Ca²⁺, M1, M2 、 M3 is one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum B1, B2, B3, and B4 are doping elements, specifically including one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).
17. The safe semi-solid battery according to claim 15, characterized in that: The chemical general formula of the transition metal phosphate compound is (C) z (M4 1-v B5 v )PO4, where 0 < z ≤ 1, 0 ≤ v ≤ 0.
4. C represents an active metal ion that can be deintercalated, specifically including any one or more of Li⁺, Na⁺, K⁺, Mg²⁺, Ca²⁺. M4 represents one or more transition metal elements, specifically including scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), mercury (Hg). B5 is a doping element, specifically including any one or more of aluminum (Al), cobalt (Co), magnesium (Mg), tantalum (Ta), tungsten (W), niobium (Nb), zirconium (Zr), calcium (Ca), vanadium (V), molybdenum (Mo), chromium (Cr), lanthanum (La), scandium (Sc), lutetium (Lu), yttrium (Y), and boron (B).
18. The safe semi-solid battery according to claim 14, characterized in that: The positive electrode conductive agent is selected from carbon materials, metal materials or materials prepared by conductive in-situ curing.
19. The safe semi-solid battery according to claim 14, characterized in that: The positive electrode current collector is a metal foil layer selected from any one of aluminum, zinc, magnesium, titanium, nickel and copper.
20. The safe semi-solid battery according to claim 13, characterized in that: The negative electrode sheet comprises a negative electrode active material, a negative electrode binder, a negative electrode conductor, and a negative electrode current collector.
21. The safe semi-solid battery according to claim 20, characterized in that: The negative electrode active material may be provided with a coating on its surface, or may be mixed with another compound having a coating.
22. The safe semi-solid battery according to claim 21, characterized in that: The coating is at least one of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxyl of a coating element, a carbonate or a nitrate or a phosphate or a borate of a coating element, and a hydroxycarbonate of a coating element.
23. The safe semi-solid battery according to claim 22, characterized in that: The coating element compound is amorphous or crystalline.
24. The safe semi-solid battery according to claim 13, characterized in that: The separator is provided with at least one surface porous layer.
25. The safe semi-solid battery according to claim 24, characterized in that: The porous layer includes inorganic particles and a porous layer binder.
26. The safe semi-solid battery according to claim 13, characterized in that: The thickness of the isolation film layer is selected from 12 μm to 20 μm.
27. The safe semi-solid battery according to claim 13, characterized in that: The safe semi-solid battery is prepared by the following method: The battery is prepared by conventional methods. After the battery is formed, a low-impedance composite electrolyte is injected into the battery by a secondary liquid injection method, and polymerized and cured at 45°C to 75°C for 2h to 20h to obtain a safe semi-solid battery.
28. The safe semi-solid battery according to claim 27, characterized in that: The battery prepared by the conventional method contains a single injection electrolyte.
29. The safe semi-solid battery according to claim 28, characterized in that: The mass ratio of the primary injection electrolyte to the low-impedance composite electrolyte is 1:0.24-1:0.
35.
30. The safe semi-solid battery according to claim 27, characterized in that: The curing temperature is selected from 50°C to 70°C, and the curing time is selected from 3h to 10h.
Citation Information
Patent Citations
Non-aqueous electrolyte solution for lithium secondary battery and lithium secondary battery including same
CN117916925A
Whole solid state / gelatin polymer solid electrolyte and its dedicated polymer and preparation method
CN1880354A